Journal on Data Semantics XI - Hutchison, David; Kanade, Takeo; Kittler, Josef; Halpin, Terry; Staab, Steffen; Svatek, Vojtech; Shvaiko, Pavel; Roddick, John F (Lecture Notes in Computer Science, 2008)
This publication features notable work that addresses research and development on issues related to data semantics. Coverage ranges from theories supporting the formal definition of semantic content to innovative domain-specific applications.